2011
DOI: 10.1158/1078-0432.ccr-10-3349
|View full text |Cite
|
Sign up to set email alerts
|

BRAF Activation Induces Transformation and Then Senescence in Human Neural Stem Cells: A Pilocytic Astrocytoma Model

Abstract: Purpose BRAF is frequently activated by gene fusion or point mutation in pilocytic astrocytoma, the most common pediatric brain tumor. We investigated the functional effect of constitutive BRAF activation in normal human neural stem and progenitor cells to determine its role in tumor induction in the brain. Experimental Design The constitutively active BRAFV600E allele was introduced into human neurospheres, and its effects on MAPK (mitogen-activated protein kinase) signaling, proliferation, soft agarose col… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
149
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(157 citation statements)
references
References 36 publications
6
149
0
2
Order By: Relevance
“…(*) P < 0.05; (**) P < 0.01; (***) P < 0.001. gliogenesis (Lee et al 2010(Lee et al , 2012. Consistent with prior BRAF results (Raabe et al 2011) and our recent findings regarding NSC brain region heterogeneity (Lee et al 2012), no change in neocortex NSC proliferation was seen following f-BRAF expression (Supplemental Fig. S2F).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…(*) P < 0.05; (**) P < 0.01; (***) P < 0.001. gliogenesis (Lee et al 2010(Lee et al , 2012. Consistent with prior BRAF results (Raabe et al 2011) and our recent findings regarding NSC brain region heterogeneity (Lee et al 2012), no change in neocortex NSC proliferation was seen following f-BRAF expression (Supplemental Fig. S2F).…”
Section: Resultssupporting
confidence: 89%
“…Although f-BRAF can transform NIH3T3 cells (Jones et al 2008), previous studies have demonstrated that BRAF does not increase astrocyte proliferation (Jacob et al 2009), induces senescence of astrocytes (Jacob et al 2011) and neural stem cells (NSCs) in vitro (Raabe et al 2011), and does not result in gliomagenesis when ectopically expressed in mouse brains in vivo (Robinson et al 2010).…”
mentioning
confidence: 99%
“…Indeed, a worse clinical outcome has been reported for pilocytic astrocytoma lacking CDKN2A expression. 42 The extent of follow-up in our study permitted only limited evaluation of survival and correlation with the molecular features of pilocytic astrocytoma of the optic nerve, and future studies will be needed to address the relationship between CDKN2A activation and clinical behavior in these tumors. Nevertheless, the presence of an active MAPK pathway and indirect evidence of increased oncogene-induced senescence in pilocytic astrocytoma of the optic nerve can explain their indolent behavior.…”
Section: Modern Pathology (2013) 26 1279-1287mentioning
confidence: 98%
“…INK4a show significantly shorter survival or aggressive behavior (15,16). Rare cases of acquired melanocytic nevi progress to malignant melanoma when they acquire additional mutations (8).…”
Section: Ink4amentioning
confidence: 99%